From Tower to the Bastion - Christof Krauskopf; Peter Purton (Fasciculi Archaeologiae Historicae)
The authors set out the key turning points in the evolution of defensive architecture in response to the appearance of firearms in the 1st quarter of the 14th century in Europe, for both attack and defence. Between the first adaptations to defences during the middle of the 14th century to the emergence of geometric whole defensive systems based on low-lying bastions and interconnected outworks in the 16th century, there was a long period of evolution, experimentation and development, responding to continuous improvement in the range and destructive power of gunpowder artillery. New designs of castles, fortresses and town walls focussed on the need to shield high medieval walls and towers against the power of the gun, but also on how to mount guns on defences and integrate loop holes to keep an attacker as far away as possible. Ideas diffused rapidly across Europe and the Muslim world. Factors such as the builder’s wealth and the purpose of the fortress also determined what was constructed.